Markov prediction based handover in dynamic ultra dense network - Qingmin MENG; Yuanyuan ZHAO; Wenjing YUE; Yulong ZOU; Xiaoming WANG (Tongxin xuebao)
In order to solve the problem of the communication and computational problems of large-scale machine communication in an ultra-dense cellular network,a Markov prediction based handover scheme (MPHS) was proposed.Firstly,a kind of heterogeneous network design with semi-structure and central control was considered which contains the densely deployed virtual nodes and thus realized a low cost and efficient coverage.The network can dynamically adjust the access point according to the user's mobility and network traffic.Secondly,a Markov model was constructed,and the idea of load-aware was introduced.By weighing the signal quality and the cell load,the user's next optimal access point was effectively predicted.The simulation results show the feasibility and effectiveness of the proposed scheme for cell handover predicting.